Effects of Mandatory Sexual Misconduct Training on University Campuses. (September 2022) - Htun, Mala; Jensenius, Francesca R.; Dominguez, Melanie Sayuri; Tinkler, Justine; Contreras, Carlos
The authors explore whether mandatory, universal, in-person sexual misconduct training achieves its goals to build knowledge about sexual assault and harassment and increase intentions to report episodes of assault. The authors present results from three studies with quasi-experimental designs as well as interviews with students and staff members at a diverse public university in the western United States. The surprising finding is that participating in training makes women students less likely to say they that will report experiences of sexual assault to university authorities. The training produces some small positive effects: students gain broader definitions of sexual misconduct and are less likely to endorse common rape myths, and women students express less sexist attitudes immediately after training. This study raises questions about whether one-shot training helps reduce sexual violence and increase reporting on college campuses and whether universities should invest in these types of training.